1995
DOI: 10.1366/0003702953963427
|View full text |Cite
|
Sign up to set email alerts
|

Total Lifetime Distribution Analysis for Fluorescence Fingerprinting and Characterization

Abstract: A new technique, total lifetime distribution analysis (TLDA), is described for rapid, sensitive, and accurate lifetime characterization of complex samples. Multiharmonic Fourier transform technology in a commercial, frequency-domain fluorescence lifetime instrument allows rapid acquisition of TLDA data. High sensitivity derives from the use of the entire fluorescence emission from the sample in the lifetime measurement. The maximum entropy method (MEM) provides a consistent basis for modeling of the lifetime d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…Kinetic changes of excitation and emission wavelengths of the fluorescence maxima suggest the occurrence of two major binding sites on fulvic acid, fast and slow, having half-lives of 1.3-3.9 and 34.7-69.3 s, respectively (Wu et al, 2004c). However, there are at least three binding sites on fulvic acid that have been observed with time-resolved fluorescence measurements (Cook and Langford, 1995;McGown et al, 1995;Kumke et al, 1998). For three fluorophores in fulvic acid, the lifetimes and emission wavelength maxima have been identified as follows: ~50 ps (392 nm), ~430 ps (465 nm), and 4.2 ns (512 nm) (Cook and Langford, 1995).…”
Section: Complexation Of Metal Ions With Fdommentioning
confidence: 99%
“…Kinetic changes of excitation and emission wavelengths of the fluorescence maxima suggest the occurrence of two major binding sites on fulvic acid, fast and slow, having half-lives of 1.3-3.9 and 34.7-69.3 s, respectively (Wu et al, 2004c). However, there are at least three binding sites on fulvic acid that have been observed with time-resolved fluorescence measurements (Cook and Langford, 1995;McGown et al, 1995;Kumke et al, 1998). For three fluorophores in fulvic acid, the lifetimes and emission wavelength maxima have been identified as follows: ~50 ps (392 nm), ~430 ps (465 nm), and 4.2 ns (512 nm) (Cook and Langford, 1995).…”
Section: Complexation Of Metal Ions With Fdommentioning
confidence: 99%
“…Several studies have analyzed time-resolved emission decays and reported the fluorescence lifetimes of some CDOM samples. 8,16,31−34 In these studies, either an a priori model that assumed a fixed number of emitting species (multiexponential analysis) 8,16,32−34 or a probabilistic model that did not limit the number of emitting species (lifetime distribution analysis) 31,33,34 was used to fit fluorescence decay data. In the fits to a fixed sum of exponentials, either lifetimes independent of emission wavelength or lifetimes dependent on emission wavelength have been applied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Steady state fluorescence spectroscopy has proven to be a highly sensitive technique which has been already successfully applied in the characterization of NOM [3,[5][6][7][8]. Recently, a few attempts have been made to approach the characterization of NOM and its dynamics by time-resolved fluorescence spectroscopy [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%